Edwin A. Halsey papers - Halsey, Edwin A. (Edwin Alexander), 1881-
Correspondence, clippings, printed and near-print material, financial records, campaign papers, and other material relating to Halsey's duties as secretary of the U.S. Senate and to various Democratic campaigns.
Secretary of the U.S. Senate; died 1945.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Congress. -- Senate; Democratic Party (U.S.); United States -- Politics and government -- 20th century; Secretaries, U.S. Senate